February 15, 2018

September 10, 2017

February 15, 2018

- Building Construction (50)
- Building Materials (47)
- Columns (3)
- Concrete Beam (3)
- Concrete Construction Techniques (6)
- Concrete Mix Design (27)
- Concrete Repair (27)
- Concrete Slab (3)
- Concrete Testing (2)
- Construction Equipment (11)
- Construction News (1)
- Design of Structures (11)
- Engineering Drawing (2)
- Estimation (5)
- Geotechnical engineering (4)
- Highway Engineering (8)
- Innovations (26)
- Material Testing (9)
- Matrix Analysis of Structures (2)
- Mechanical Engineering (3)
- Transportation Engineering (4)

Ram Chand
August 21, 2019

Simple bending or pure bending is defined as the phenomenon of development of stresses throughout the length of the beam due to the action of bending moment exclusively. The stresses development throughout the length of the beam is called as **bending stress.**

In this article, we will discuss the simple bending theory, the assumptions in the theory followed by the derivation to determine the** bending stress or the Bending equation.**

### Simple Bending Theory

This beam section AB is said to be in the condition of simple bending or pure bending.

In this article, we will discuss the simple bending theory, the assumptions in the theory followed by the derivation to determine the

Beam Construction; Image Courtesy: Molin Precast Products |

Simple bending can be explained by the below beam and load arrangement. As shown in the figure, from the BM diagram of the corresponding beam arrangement have constant Bending moment along the beam length AB and the SF has nothing to contribute to that length.

Fig.1. Simple Bending Theory Explanation |

M/I = E/R = 𝛔/y

- The material of the beam is homogeneous and isotropic
- The transverse section of the beam remains plane before and after bending.
- The value of young's modulus is the same in tension and compression
- The beam is initially straight and all the longitudinal filaments bend into circular arcs with a common center of curvature
- The radius of curvature is large compared with the dimensions of the cross-section.
- Every layer of the beam is free to expand or contract independent of the layer below it.

As shown in the figure above, consider a beam small beam section ABCD with a length of dx. The N-N forms the neutral axis of the beam element. Section AB and CD are perpendicular to the neutral axis N-N. The beam element under the action of bending gets deformed as shown in figure-2(b).

The layers of the beam before bending do not remain the same after bending. The layer AC and BD have deformed to A'C' and B'D' respectively. The layer gets shorten at top and expands at the bottom layer. The beam layer does not undergo any change at the neutral layer. This means,

As we move from the bottom layer to the neutral layer, the length of layers decreases. Hence, the increase or decrease of length of the layer is dependent on its distance from the neutral axis. This theory of bending is called the theory of simple bending.

Given:

The radius of the Neutral layer = R

The angle subtended by A'B' and C'D' at O = θ

The radius of the Neutral layer = R

The angle subtended by A'B' and C'D' at O = θ

Then,

Strain Variation along Depth of Beam

Original length of layer = EF = dx;

Original length of Neutral layer = NN = N'N' = dx

Hence, the strain in the layer EF is directly proportional to the distance of the layer from the neutral axis. This relation shows the variation of the strain along the depth of the beam. The variation of strain is linear.

Stress Variation along Depth of Beam Young's modulus E = stress in layer EF / Strain in layer

Strain Variation along Depth of Beam

Original length of layer = EF = dx;

Original length of Neutral layer = NN = N'N' = dx

From Figure,

N'N' = R x θ = dx

E'F' = (R + y ) θ

Strain in the layer EF = Increase in the length of layer EF / (Original Length)

= (E'F' -EF)/EF

= ( (R +y) θ - (Rx θ))/dx

= (R θ + y θ - R θ)/ dx

= y θ/dx

= y θ/R θ

=y/R

N'N' = R x θ = dx

E'F' = (R + y ) θ

Strain in the layer EF = Increase in the length of layer EF / (Original Length)

= (E'F' -EF)/EF

= ( (R +y) θ - (Rx θ))/dx

= (R θ + y θ - R θ)/ dx

= y θ/dx

= y θ/R θ

=y/R

Hence, the strain in the layer EF is directly proportional to the distance of the layer from the neutral axis. This relation shows the variation of the strain along the depth of the beam. The variation of strain is linear.

Stress Variation along Depth of Beam Young's modulus E = stress in layer EF / Strain in layer

E = 𝛔 /(y/R)

=> E = 𝜎R/y

=> E/R = 𝛔/y

Moment of Resistance The layer above the neutral axis experience compressive force Fc and the layers below the neutral axis experiences tensile force Ft.

=> E = 𝜎R/y

=> E/R = 𝛔/y

Moment of Resistance The layer above the neutral axis experience compressive force Fc and the layers below the neutral axis experiences tensile force Ft.

For equilibrium:

Fc= Ft

The moments caused due to these internal forces must be equal and opposite the BM caused at section f the beam.

Moment of resistance is defined as the algebraic sum of moments about the neutral axis of the internal forces developed in the beam.

If the cross-sectional area of the element is dA, then

Total Moment of resistance M = ∫ (𝛔 dA . y) = ∫(Ey. y. dA)/R

=> M = (E/R)∫y^2 . dA

Moment of Inertia I = ∫y^2. dA

Hence, we get

M = EI/R

Hence, we get

**M/I = E/R = 𝛔/y ;**

The above equation is called as the Bending Equation/ Flexural Formula.

**Also Read**

Fc= Ft

The moments caused due to these internal forces must be equal and opposite the BM caused at section f the beam.

Moment of resistance is defined as the algebraic sum of moments about the neutral axis of the internal forces developed in the beam.

If the cross-sectional area of the element is dA, then

Total Moment of resistance M = ∫ (𝛔 dA . y) = ∫(Ey. y. dA)/R

=> M = (E/R)∫y^2 . dA

Moment of Inertia I = ∫y^2. dA

Hence, we get

M = EI/R

Hence, we get

The above equation is called as the Bending Equation/ Flexural Formula.

Principle of Statics in Structural Analysis | Conditions of Static Equilibrium |Sign Convention

What is Structural Equilibrium? | Translational & Rotational equilibrium

Introduction to structural Analysis

Structural Analysis-Material Properties and Boundary Conditions

Structural Analysis- Idealizing a Structure for Analysis -Part 3

What is Structural Equilibrium? | Translational & Rotational equilibrium

Introduction to structural Analysis

Structural Analysis-Material Properties and Boundary Conditions

Structural Analysis- Idealizing a Structure for Analysis -Part 3

Reactions

September 10, 2017

February 15, 2018

September 13, 2017

March 22, 2019

June 26, 2017

- Ram Chand
- Hi, I am Ram Chand. I am a structural engineering professional. Prodyogi is a blog started to share knowledge on civil engineering for constructors around the world. Each article in Prodyogi is explained precisely to make it simple for everyone to understand. Kindly support Prodyogi and Join the community so that we can learn together.

Created By SoraTemplates | Distributed By Gooyaabi Templates

Close Menu

## 0 Comments